Notes on the genus Dolichothrombium (Acari: Prostigmata: Trombidiidae)with description of a new species - Mąkol, Joanna; Sevsay, Sevgi (Zootaxa, 2011)
A new species, Dolichothrombium anatoliae sp. nov., is described based on active postlarval forms and larvae. Larvae of Dolichothrombium Feider, 1945 were obtained for the first time by experimental rearing from field-collected females. Azaritrombium Saboori, Bagheri et Haddad Irani-nejad, 2005, hitherto known exclusively from larvae, is regarded as a junior synonym of Dolichothrombium. Diagnoses of active postlarval forms and larvae are given and all species assigned to Dolichothrombium are listed. An identification key to active postlarval forms and larvae is provided.